2020
DOI: 10.1002/ccd.29239
|View full text |Cite
|
Sign up to set email alerts
|

Predicting need for pacemaker implantation early and late after transcatheter aortic valve implantation

Abstract: Objectives To identify associations with either early or late permanent pacemaker (PPM) implantation after transcatheter aortic valve replacement (TAVR) in order to develop an easily interpretable management algorithm. Background Injury to the conduction system after TAVR occasionally requires PPM. There is limited data on how to identify which patients will require PPM, particularly after discharge from index hospitalization after TAVR. Methods All patients having undergone TAVR at the University of North Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…Demographic and clinical characteristics that have been associated with post-TAVR PPM implantation include male gender and a history of AF. [ 12 , 19 , 20 ] Our group previously analysed 62,083 TAVR patients from 2012 to 2017 from the Nationwide Readmissions Database in the US which further demonstrated that a history of diabetes, acute kidney injury, chronic kidney disease, dementia and hypertension were independently associated with PPM implantation within 30 days of TAVR ( Figure 2 ). [ 16 ] Pacemaker implantations post-TAVR were also stratified by whether they occurred early (prior to discharge from TAVR hospitalisation) or late (after discharge).…”
Section: Preprocedural Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Demographic and clinical characteristics that have been associated with post-TAVR PPM implantation include male gender and a history of AF. [ 12 , 19 , 20 ] Our group previously analysed 62,083 TAVR patients from 2012 to 2017 from the Nationwide Readmissions Database in the US which further demonstrated that a history of diabetes, acute kidney injury, chronic kidney disease, dementia and hypertension were independently associated with PPM implantation within 30 days of TAVR ( Figure 2 ). [ 16 ] Pacemaker implantations post-TAVR were also stratified by whether they occurred early (prior to discharge from TAVR hospitalisation) or late (after discharge).…”
Section: Preprocedural Factorsmentioning
confidence: 99%
“…Most of this transient pacing requirement resolves on its own but it has also been shown to be associated with higher risk of the need for long-term pacing. [ 12 , 26 ] Patients suspected to be in need of temporary pacing after the TAVR procedure should be considered for an internal jugular approach for the temporary pacing wire. This can improve patient comfort as observation periods with temporary pacing wires in place can go extend to 48 hours.…”
Section: Timing Of Heart Blockmentioning
confidence: 99%
See 3 more Smart Citations